Sustainability practices in Malaysian grocery retail industry - Vijayan, Gowri (2015)
Malaysia is in the midst of a nationwide green movement to combat the environmental problems plaguing the nation. Water pollution, air pollution, deforestation, soil and coastal erosion, overfishing, and solid waste mismanagement are some of the many problems faced by the nation. However, solid waste mismanagement has become a major environmental issue of concern to the government. Overflowing capacity of landfills, limited recycling centers, poor waste collection system, and weak policies on waste management elevate the seriousness of this situation. The Malaysian government‟s solution to this problem is shifting from depending solely on environmental policies to preventive steps for calculation and management of pollution,through holistic focus on introducing sustainability and 3R (reduce, reuse, recycle) campaigns to businesses and consumers. With the changing governmental stand towards environmental conservation, industries can no longer avoid getting into sustainability practices for their operations. The grocery retail is one of the largest service industries in Malaysia, and also a major contributor to environmental pollution in the nation. The environmental effects from retail operations in this industry includes solid waste generation, energy use, water pollution, and air pollution. However, the grocery retail industry is in a unique position to also green its services. Retailers can effectively implement sustainability along upstream and downstream ends of supply chain. They are widely recognized as changeagents for introducing sustainability into supply chains. The retail stores can play a role in reducing food wastage, implementing better waste management practices, promotion of green products, while introducing more sustainability practices into the food supply chain. Thereby, it is imperative to understand sustainability as practiced in this industry. However, the Malaysian grocery retail industry is heavily fragmented, with 56% provision stores, 43% hypermarkets and supermarkets, and 1% convenience stores. This fragmentation makes monitoring of sustainability both difficult and critical for sustainable development in the industry. It is essential to identify the practices that retail formats identify as sustainable, and to evaluate their level of sustainability based on its implementation. Specifically, the implementation of reverse logistics in the Malaysian retail industry needs to be evaluated, due to its contribution to waste management among other benefits. Since business decisions on change often depends on value added benefits, the evaluation of contribution of sustainability to firm performance is critical for sustainable development. A study on mediation is critical to study the effect of intervening variables on sustainability implementation. The verification of such an effect could be used by regulatory bodies for policy development and evaluation. The large concentration of provision stores in this industry (56%), followed by wide spread distribution across the nation makes it a critical agent to sustainable development in the industry. Also, the government‟s focus on Program Transformasi Kedai Runcit or Small Retailer Transformation Program (TUKAR) makes information on sustainability in provision stores critical. However, such studies on sustainability, focused across retail formats in the Malaysian grocery retail industry are limited. Especially since the grocery retail industry is fragmented, information on sustainability as understood and practiced by all the major retail formats is required to summarize on sustainability in the retail industry. The current research was carried out to study the sustainability as implemented in this industry. A post-positivist approach was adopted in the study, incorporating the Stakeholder Theory to confirm the predictors to sustainability implementation in stores. The level of sustainability across retail formats were categorized using the Three Tiers Ranking System. Descriptive statistics was used to categorize the level of sustainability, environmental concern of retailers, and reverse logistics in stores. The influencers to sustainability implementation were identified across stakeholder pressure, CSR, economic, and environmental factors, and barriers that hinder sustainability in business. Mean ranking, confirmatory factor analysis (CFA), and mediation were used to evaluate and interpret all possible effects of these factors to eco-friendly and reverse logistics implementation in retail stores. The contributions of eco-friendly and reverse logistics to firm performance were evaluated for managerial implications using importance-performance matrix analysis (IPMA). The associative relationship between firmographic characteristics of retail stores and sustainability implementation across the formats were tested using chi-square analysis. Mediation analysis using bootstrapping method was used to estimate the effects of intervening variables to reverse logistics implementation and firm performance. Content analysis was used to verify the factors found significant to sustainability implementation in provision stores. The study interviewed 375 respondents using a structured questionnaire to understand sustainability in the industry. The respondent stores included representatives from the four major retail formats, namely provision stores, supermarkets, hypermarkets, and convenience stores. The stores identified waste management issues, water crisis, and energy crisis to influence their store operations. Majority of the stores were found to be unfamiliar with the Malaysian government‟s Solid Waste and Public Cleansing Management Act 2007 (SWPCMA 2007), though 3R campaigns were familiar to them. Product take-back policy was adopted by majority of the retailers, mainly as per supplier instructions for returns. The study showed that Tier 1 eco-friendly practices like reducing energy consumption and energy saving activities were mainly followed by the retail formats. The green practices of local supplier support, green consumer research, and promotion of green products in stores were found to be highly practiced by hypermarkets, and supermarkets. Hypermarkets were the major practitioners of Tier 3 sustainability practices, followed by convenience stores. The firmographic characteristics of store location, years of store operation, and annual sales were found to influence the implementation of sustainability in the retail industry. The predictors CSR and barriers to implementation were found to significantly influence the implementation of Tier 1 sustainability practices in retail stores. The predictors CSR, barriers, stakeholder pressure, and implementation of Tier 1 sustainability practices were found to significantly influence the implementation of reverse logistics practices by retail stores. The implementation of Tier 1 practices was found to contribute more to the firm performance. However, the implementation of reverse logistics practices were found to reduce the effect of Tier 1 practices to the firm performance. This could be because of increased resource commitment required for execution of the reverse logistics operations at the retail end of the supply chain. Since Tier 1 practices were found important to the firm performance, the implementation of reverse logistics could be considered a hindrance. But, it was found that reverse logistics contributed greatly to operational firm performance. Also, the implementation of Tier 1 practices was found to reduce the pressure on retailers to turn sustainable. This could be due to the familiarity among stakeholders on Tier 1 practices and its implications over reverse logistics. Therefore, in order to ensure reverse logistics implementation, the government has to develop specific policies for implementation of reverse logistics by grocery retail stores. Content analysis revealed governmental, competitor, NGO pressures, and barriers to significantly influence the implementation of sustainability in provision stores. Provision stores focused on competitor practices to retain their markets, to meet consumer needs, and as temporary experts for sustainability adoption. Government played the most important role in influencing the implementation of reverse logistics practices in the provision stores. Therefore, the government could turn the provision stores green with stricter policies and economic incentives. The study conducted a detailed evaluation of sustainability as implemented across retail formats. All possible interactions between interacting variables provided an insight into the relationship between intervening variables and their influence on sustainability. These observations could be used by regulatory bodies and top management for policy development. The Three Tier Ranking System used in this study could be used by other agencies to monitor the level of sustainability across retail formats. The academicians could use this study as a base for confirmation based and post-positivist research, and pave the way for extensive sustainability studies in the food sector. In the long run, the combination of increased academic awareness and specific policies could pave the way for voluntary practices and a greener, cleaner, and healthier Malaysia.